Letramentos acadêmicos em um curso de Letras/Inglês: o discurso do Projeto Político Pedagógico e o discurso de alunos e egressos - Preischardt, Betyna Faccin (2015)
The objective of this research is to analyze critically the discourses from Political Pedagogical Project (PPP) and from students and graduates in an Undergraduation Course in English Language (CLI) from a Brazilian southern university about the academic literacies practices and events in professional teaching. For that, we try to identify the academic literacies practices predicted in PPP to students and academic literacies events by students and graduates experience reports. We based ourselves on concepts that would enable us to analyze the PPP and students and graduates discourses about the academic literacies. So, we chose the theoretical and methodological approach Critical Genre Analysis (MEURER, 2002), that interweaves three social theories, Critical Discourse Analysis (FAIRCLOUGH, 1992, 2003), Sociorretórica (MILLER, 1984; SWALES, 1990; BAZERMAN, 2005) and Systemic Functional Grammar (HALLIDAY; MATTHIESSEN, 2004). In addition, conversations about academic literacies (BARTON, 1991; LEA; STREET, 2006), the concept of Legitimate Peripheral Participation (LPP) (LAVE; WENGER, 1991) and the theoretical and methodological approach ethnography (SAVILLE-TROIKE, 1989) allowed us to analyze and discuss the PPP and students and graduates discourses. To unveil the PPP discourse, we analyze the Egress Profile and Curriculum sections and to the discourse from students and graduates we developed semi-structured questionnaires from PPP excerpts. On the PPP analysis, we identify the academic literacies practices predicted to students and graduates in the CLI. Three academic literacies practices are recognized in the PPP: participation in projects, text production and consumption and professional performance. These three practices were described by identifying the skills and competences predicted for egress and the disciplines. We also recognize that the text production and consumption seems to carry a central role among the practices participation in projects and professional performance. In the analysis of questionnaires, from the search for textual rich features in meaning (BARTON, 2002), we noted four academic literacies practices: participation in the activities of the courses in CLI, participation in projects, participation in scientific events and professional performance. These four practices are recognized in the students and graduates discourse by reporting the academic literacies events they said engage to and participate in. Students and graduates more clearly described the events that constituted practices in that were engaging in the activities of CLI. It seemed also that as these students participated in these events, (re)constitute themselves as English teachers, from the recognition of this context and the individuals involved in these events (FAIRCLOUGH, 2010).